Risk factors for incidence of trachomatous scarring in a cohort of women in low endemic district. Issue 4 (6th January 2018) - Karani, Rabia; Wolle, Meraf; Mkocha, Harran; Muñoz, Beatriz; West, Sheila K
Abstract : Background/aims: To determine the incidence of scarring in women in a trachoma low endemic district of rural Tanzania and to determine the effects of lifetime cooking fire exposure and markers of lower socioeconomic status on incidence of scarring in these women. Methods: A prospective cohort study was conducted over a 3.5-year period from 2013 to 2016 in 48 villages in Kongwa, Tanzania where trachoma at baseline was 5.2% in children. A random sample of 2966 women aged 15 and older who were at risk for incident scarring were eligible for follow-up. Data on demographic factors, cooking fire exposure and trachomatous scarring were gathered at baseline and follow-up. An index of lifetime exposure to cooking fire exposure was created and bivariate analysis, age-adjusted logistic regression and multivariable logistic models were used to look for associations of demographic factors and cooking fire exposure with incident trachomatous scarring. Results: The cumulative incidence of scarring was 7.1% or 2.0% per year. Incidence of scarring increased with age and exposure to markers of lower socioeconomic status. A multivariable logistic regression model adjusting for confounding factors did not find an association between lifetime cooking fire exposure and incidence of scarring (OR=0.92; 95% CI 0.68 to 1.24, P=0.58). Conclusions: There was still incident scarring in women in Tanzania despite low rates of active trachoma. There was no association between exposure to cooking fires and incident scarring. More research is needed to understand the factors that contribute to new scarring in these women.